KONFLIK PERAN GANDA DAN KEBERFUNGSIAN KELUARGA PADA IBU YANG BEKERJA - ZARINA AKBAR; KHARISMA KARTIKA (Journal of Research and Measurement in Psychology, 2016)
This research aimed to determine the influence of work-family conflict to the family functioning between working mother. The research using quantitative. The sample were 100 working mother (n = 100) by using the method purposive sampling . The data using a questionnaire with an instrument work- family conflict scales (40 item) and family assessment device (52 item). Statistical data is done by using Rasch Model in the form of software Winstep and SPSS 23.0. Results of research indicate that there is influence of work-family conflict to the family functioning between working mother. The value of Fhit> Ftabel (59,08> 3,94) and R square value equal to 0, 376.